Development of an Ozone-Assisted Sample Preparation Method for the Determination of Cu and Zn in Rice Samples - Mariela Pistón; Ignacio Machado; Esteban Rodríguez-Arce; Isabel Dol (Journal of Analytical Methods in Chemistry)
A green analytical method for the determination of Cu and Zn in rice samples was developed. This method was based on an ozone-assisted extraction (OAE) in diluted acid media. A novel closed system was designed for this purpose that allowed four simultaneous sample treatments being safe for the laboratory environment. The method consisted in 0.5 g of the sample, 15 minutes of ozonation, and 3 minutes of centrifugation. The obtained supernatant was ready for Cu and Zn determinations by flame atomic absorption spectrometry. Detection limits were 0.20 and 0.08 mg kg−1 for Cu and Zn, respectively, with a precision (RSD) better than 5% for both elements. A certified reference material of rice flour was analyzed for trueness evaluation, and the mean recoveries (%) were 100.4 (Cu) and 95.9 (Zn). Several commercial rice samples were analyzed using this method, and the results were compared with those obtained using traditional microwave-assisted digestion (MAE). Both methods yielded comparable results. Cu and Zn levels were in accordance with reported values in other regions. The OAE resulted to be simple and economical and with results equivalent with those obtained using traditional sample preparation procedures as MAE with the advantage of being in good agreement with the principles of green analytical chemistry.